Thermoplastic elastomer compositions having improved metal adhesion properties
By using a thermoplastic elastomer composition containing polypropylene, thermoplastic polyurethane and modified hydrogenated styrene-based block copolymer in the steel strip sheath material, the problem of insufficient adhesion of thermoplastic polymers on the steel strip surface in the prior art is solved, and higher adhesion and durability are achieved.
Patent Information
- Application Number
- CN202411392788.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-06
- Filing Date
- 2024-10-08
- Publication Date
- 2025-04-08
AI Technical Summary
The existing thermoplastic polymers have insufficient adhesion to the steel strip surface, resulting in poor long-term stability under external stress and are prone to degradation during service life, resulting in deterioration of surface, physical and mechanical properties over time.
A thermoplastic elastomer composition is used, which comprises 8-60 wt% polypropylene, 2-12 wt% thermoplastic polyurethane, 0-55 wt% modified hydrogenated styrene-type block copolymer, and 38-75 wt% hydrogenated styrene-type block copolymer to improve adhesion to metal surfaces.
Through the improved composition, the adhesion and durability to the metal surface are significantly improved, and the risk of degradation of polymers during use is reduced, thereby improving the long-term stability and performance of the steel belt sheath material.
Smart Images

Figure BDA0005072897420000131
Abstract
Description
Technical Field
[0001] The present invention relates to a thermoplastic elastomer composition comprising a hydrogenated styrenic block copolymer for improving metal adhesion, and articles made therefrom, such as a sheath material for elevator cables. Background Art
[0002] Coated steel belts (CSB) are widely used in elevator systems due to their favorable properties. The reliability and safety of the said steel belts are the most important factors in elevator operation. Steel wires coated with thermoplastics have wider applications in science and engineering. Polymer coatings of steel wires and steel strands have different purposes, however, the undisputed requirement of polymer coating of steel wires is to achieve a better balance between weight reduction, strength and flexibility, which largely depends on a good control of the adhesion between steel and polymer and vice versa.
[0003] The most common / traditional polymers used as jacket materials in CSB technology are polyamides, polyurethanes or thermoplastic vulcanizates (TPVs). These traditional polymers adhere to the steel belt. However, steel-polymer interfaces often suffer from poor adhesion strength due to weak interactions between the steel and polymer surfaces, which undermines their long-term stability under external stresses. Some of these polymers face degradation issues during their service life, resulting in deterioration of surface, physical and mechanical properties over time.
[0004] There is a need to improve the adhesion of thermoplastic compounds to metal surfaces. Thermoplastic elastomers have improved adhesion to metal surfaces due to their improved tensile properties and flow behavior for processability. SUMMARY OF THE INVENTION
[0005] In one aspect, the present invention relates to a thermoplastic elastomer composition comprising, consisting essentially of, or consisting of: 8-60 wt% of a thermoplastic elastomer having a melt flow rate of 3-60 g / 10 min at 230° C. and 2.16 kg load as measured according to ASTM D1238 and a melt flow rate of <1 g / cm 3 The density of polypropylene, 2-12wt% has 1-1.2g / cm 3The invention relates to a thermoplastic polyurethane having a density of 0.05 wt %, a modified hydrogenated styrene block copolymer of 0-55 wt %, and a hydrogenated styrene block copolymer of 38-75 wt %. The hydrogenated styrene block copolymer is represented by at least one formula selected from SE / B / SS, (SE / B / S)nX and (SE / B / S)nX, wherein n is an integer of 2-30 and X is a residue of a coupling agent. Each block S is a polymer block composed of vinyl aromatic units, and each block S has a peak molecular weight of 5-40 kg / mol measured according to ASTM 5296-19. Each block E / B / S is a copolymer block composed of ethylene units, butene units and vinyl aromatic units, and each block E / B / S has a peak molecular weight of 35-300 kg / mol measured according to ASTM 5296-19. The molar ratio between the ethylene units and the butene units of the hydrogenated styrene block copolymer is 10:90-65:35 (measured by 1 HNMR measurement), residual unsaturation of <0.5 meq / g, total content of vinyl aromatic units of 25-65 wt%, peak molecular weight of 40-500 kg / mol. The thermoplastic elastomer composition has a melt flow rate of 1.0-45 g / 10 min at 230° C. and 2.16 kg load measured according to ASTM D-1238, a Shore A hardness of 40-100 measured at 10 seconds according to ASTM D-2240, and a peel force to a galvanized steel substrate of 45-300 gf / 25 mm measured according to ASTM D-3330.
[0006] In a second aspect, the amount of the modified hydrogenated styrenic block copolymer is 2-15 wt%.
[0007] In a third aspect, the modified hydrogenated styrenic block copolymer comprises at least one functional group selected from the group consisting of carboxylic acid groups and salts thereof, anhydrides, esters, imide groups, amide groups, epoxy groups, and acid chlorides.
[0008] In a fourth aspect, the modified hydrogenated styrenic block copolymer is a maleic anhydride functionalized hydrogenated styrenic block copolymer having 0.1 to 10 wt % maleic anhydride, based on the total weight of the modified hydrogenated styrenic block copolymer.
[0009] In a fifth aspect, the present invention relates to an article comprising the thermoplastic elastomer composition, which is used as an elevator pulley lining, a belt, a synchronous belt, a conveyor, a seamless belt, a transmission separation device or a charging device. DETAILED DESCRIPTION OF THE INVENTION
[0010] The following terms will be used throughout this specification.
[0011] “Consisting essentially of…” means that the claimed composition mainly contains the specified materials, and is allowed to contain additional components that do not materially affect the novel characteristics or functions of the claimed invention. If present, the content of the additional components is <30%, or <20%, or <10%.
[0012] “At least one of A, B, and C” or “any one of [A, B, and C]” refers to a single member thereof, more than one member thereof, or a combination of members thereof. For example, at least one of A, B, and C includes, for example, only A, only B, or only C, and any other combination of A and B, A and C, B and C, or A, B and C, or A, B and C.
[0013] Embodiments presented as "A, B, or C" should be interpreted to include only A, only B, only C, "A or B", "A or C", "B or C", or "A, B, or C".
[0014] "Any one of A, B or C" means one option among A, B or C, for example, only A, only B or only C.
[0015] "Any one of A, B and C" means one or more options of A, B and C, such as only A, only B, only C, A and B, A and C, A, B and C, etc.
[0016] "Copolymer" refers to a polymer derived from more than one monomeric species.
[0017] "Block copolymer" refers to a copolymer containing more than one monomeric species, wherein the monomers are present in blocks. Each block is composed of a group of monomeric units that are different from the monomer groups of the surrounding blocks connected in the same block copolymer. Each block can be composed of a homopolymer or a random copolymer.
[0018] The "polystyrene content" or PSC or "total vinyl aromatic content" of a block copolymer refers to the weight percent of vinyl aromatic monomer (e.g., styrene) in the block copolymer, calculated by summing the molecular weights of all vinyl aromatic units divided by the total molecular weight of the block copolymer. The total vinyl aromatic content (PSC) can be determined using any suitable method, such as proton nuclear magnetic resonance spectroscopy ( 1 HNMR).
[0019] "Monovinyl aromatic", "monoalkenyl arene" or "vinyl aromatic" refers to an organic compound containing one carbon-carbon double bond, at least one aromatic moiety and a total of 8 to 18 carbon atoms (e.g., 8 to 12 carbon atoms). Examples include any of styrene, o-methylstyrene, p-methylstyrene, p-tert-butylstyrene, 2,4-dimethylstyrene, α-methylstyrene, vinylnaphthalene, vinyltoluene, vinylxylene, or mixtures thereof. In some embodiments, the monoalkenyl aromatic hydrocarbon block comprises substantially pure monoalkenyl aromatic hydrocarbon monomers. In some embodiments, styrene is the major component, with a small amount (less than 10 wt%) of a structurally related vinyl aromatic monomer, such as o-methylstyrene, p-methylstyrene, p-tert-butylstyrene, 2,4-dimethylstyrene, α-methylstyrene, vinylnaphthalene, vinyltoluene, vinylxylene, or combinations thereof. In some embodiments, only styrene is used.
[0020] "Vinyl content" refers to the amount of conjugated diene monomers that have polymerized by 1,2-addition in the case of butadiene or by 3,4-addition in the case of isoprene (thus producing monosubstituted olefins or vinyl groups adjacent to the polymer backbone). Vinyl content can be determined by proton nuclear magnetic resonance spectroscopy ( 1 HNMR) determination.
[0021] "Molecular weight" or Mw refers to the polystyrene equivalent molecular weight of a polymer block or block copolymer in kg / mol. Mw can be determined by gel permeation chromatography (GPC) using polystyrene calibration standards, for example, according to ASTM 5296-19. The GPC detector can be an ultraviolet or refractive index detector or a combination thereof. The chromatograph is calibrated using commercially available polystyrene molecular weight standards. The Mw of a polymer determined using GPC is the polystyrene equivalent molecular weight or apparent molecular weight, measured at the peak of the GPC trace, usually referred to as the polystyrene equivalent "peak molecular weight", expressed as M p The Mw of a single GPC block can be calculated by the difference in the Mp measured before and after polymerization of the block in question. For example, the Mw of block B is the Mp of material AB minus the Mp of block A.
[0022] "Oil-free (oil-free)" refers to a composition having a paraffin oil content of <0.1 wt%, or <0.05 wt%, or <0.01 wt%, based on the total weight of the composition.
[0023] "HSBC" refers to a selectively hydrogenated styrenic block copolymer. Hydrogenated styrenic block copolymers are based on copolymerized conjugated diene and styrene monomers, wherein a significant portion of the double bonds arising from the conjugated diene units have been reduced or hydrogenated, "selective" meaning that the conjugated bonds are fully hydrogenated (e.g., >95% or >99%), and the aromatic bonds are hydrogenated to a much lower degree (e.g., 0-15%).
[0024] “Hydrogenation level” (H 2 %) refers to the saturation level of olefin double bonds in the block copolymer, which can be determined using UV-VIS spectrophotometry and / or 1 HNMR and / or by ozonolysis titration.
[0025] "Residual unsaturation (RU)" refers to the level of unsaturation, i.e., carbon-carbon double bonds per gram of block copolymer. RU can be measured using nuclear magnetic resonance (NMR). 1 HNMR) or ozonolysis titration.
[0026] The "unit" used in the concept of polymer unit or copolymer unit refers to the repeating building blocks constituting the polymer or copolymer in question. These polymer units are usually directly or indirectly related to the monomers which are polymerized or copolymerized to produce the polymer or copolymer.
[0027] The present invention relates to a thermoplastic elastomer composition having improved adhesion properties, especially to metals. The thermoplastic elastomer composition comprises, consists essentially of, or consists of at least one hydrogenated styrenic block copolymer (HSBC), polypropylene (PP), and thermoplastic polyurethane (TPU). The composition provides comparable or better properties than TPU-based compositions containing plasticizers.
[0028] Hydrogenated styrenic block copolymer (HSBC): The thermoplastic elastomer composition comprises at least one hydrogenated styrenic block copolymer (HSBC) obtained by hydrogenating a styrenic block copolymer (SBC).
[0029] In some embodiments, HSBC is any of a linear or branched (multi-arm) block copolymer comprising: at least one polymer block S derived from a vinyl aromatic monomer, and at least one block of: a) polymer block E / B, which is an ethylene / butylene block obtained by hydrogenating polymerized 1,3-butadiene monomer, or b) polymer block EP, which is an ethylene-propylene block obtained by hydrogenating polymerized isoprene monomer. The vinyl aromatic monomers may be introduced or copolymerized with 1,3-butadiene and / or isoprene monomers in any order and any distribution to form any of the configurations described.
[0030] In some embodiments, HSBC is represented by at least one formula selected from SE / B / SS, (SE / B / S)nX, (SE / B / SS)nX or SI / EP-S, (SI / EP)nX, wherein n=an integer from 2 to 7, and X is the residue of a coupling agent. Each S block is a vinyl aromatic unit. E / B / S is a copolymerized ethylene unit / butylene unit / and a vinyl aromatic unit, IP is an isoprene block, and EP is an ethylene-propylene block.
[0031] In a preferred embodiment, HSBC is represented by at least one selected from SE / B / SS, (SE / B / S)nX, (SE / B / SS)nX and mixtures thereof, wherein n=an integer from 2 to 7 and X is the residue of a coupling agent. Each S block is a vinyl aromatic block. E / B / S is a copolymer block composed of ethylene (E) units, butene (B) units and vinyl aromatic (S) units.
[0032] In some embodiments, the vinyl aromatic monomer is selected from styrene, α-methylstyrene, methylstyrene, p-methylstyrene, p-ethylstyrene, p-n-propylstyrene, p-isopropylstyrene, p-n-butylstyrene, p-sec-butylstyrene, p-isobutylstyrene, p-tert-butylstyrene, isomers of p-decylstyrene, isomers of p-dodecylstyrene, dimethylstyrene, halogenated styrenes, methoxystyrene, acetoxystyrene, vinyltoluene, isomers of vinyltoluene, vinylxylene, 4-vinylbiphenyl, vinylnaphthalene, vinylanthracene, and mixtures thereof.
[0033] In some embodiments, the molar ratio of E to B in each copolymerized E / B / S block is 10:90-65:35, or 20:80-60:40, or 25:75-55:45, which can be achieved by 1 HNMR confirmed.
[0034] In some embodiments, block E / B / S comprises 15-50, or 18-45, or 20-40 wt % 1,3-butadiene monomer introduced via 1,2-addition, based on the total weight of polymerized 1,3-butadiene monomer in block E / B / S, with the remainder introduced via 1,4-addition.
[0035] In some embodiments, based on the total weight of HSBC, block S accounts for 5-25, or 6-22, or 7-20, or 8-15 wt%, block EP accounts for 40-65, or 45-60, or 45-65 wt%, and block E / B / S accounts for 10-35, or 12-30, or 15-25 wt%.
[0036] The block S derived from polymerized vinyl aromatic monomer units may be substantially unhydrogenated. In some embodiments, the level of hydrogenation of block S is <30, or <20, or <10, or <5%, based on the total double bonds present in block S. In some embodiments, the polyisoprene block is hydrogenated to a hydrogenation level of >80, or >85, or >90, or >95, or >98, or >99, or up to 100%, based on the total double bonds present in the polyisoprene block. In some embodiments, the polybutadiene block is hydrogenated to a hydrogenation level of >80, or >85, or >90, or >95, or >98, or >99, or up to 100%, based on the total double bonds present in the polybutadiene block.
[0037] In some embodiments, the residual unsaturation or RU of the polybutadiene block is 0-0.5 meq / g, or 0.05-0.5 meq / g, or <0.5 meq / g, or <0.4 meq / g, or <0.3 meq / g, or <0.2 meq / g, or <0.1 meq / g based on the total double bonds present in the polybutadiene block.
[0038] In some embodiments, the peak molecular weight of each polymer block S is 2-35 kg / mol, or 5-40 kg / mol, or 7-35 kg / mol, or 9-30 kg / mol, or at least 9.0 kg / mol, or at least 8.5 kg / mol, or at least 5.0 kg / mol. In some embodiments, the peak molecular weight of the block E / B / S is 35-300 kg / mol, or 40-250 kg / mol, or 45-225 kg / mol, or 50-200 kg / mol, or 60-180 kg / mol, or >35 kg / mol, or >40 kg / mol, or <45 kg / mol, or <300 kg / mol. In some embodiments, the peak molecular weight of the E / B / S block is determined by subtracting the peak molecular weight of the S block from the peak molecular weight of SE / B / S.
[0039] In some embodiments, the average 1,2-vinyl or 3,4-vinyl content of HSBC is 25-90 wt%, or 25-80 wt%, or 25-75 wt%, or 20-65 wt%, or 25-55 wt%, or 30-50 wt%, or >15 wt%, or >20 wt%, or <75 wt%, or <90 wt%, or <80 wt%. The vinyl content can be reduced by 1 HNMR measurements.
[0040] In some embodiments, HSBCs having a (SE / B / S)nX or (SE / B / SS)nX structure have a coupling efficiency of >50%, or >60%, or >70%, or >80%, or >90%.
[0041] In some embodiments, the total vinyl aromatic content (PSC) of the HSBC is >15 wt%, or 20-70 wt%, or 25-65 wt%, or 30-55 wt%, or <70 wt%, or <65 wt%, or <60 wt%.
[0042] In some embodiments, the peak molecular weight (Mp) of the HSBC is 40-500 kg / mol, or 60-400 kg / mol, or 75-250 kg / mol, or <400 kg / mol, or <300 kg / mol, or <200 kg / mol.
[0043] In some embodiments, the HSBC content is 40-80 wt%, or 38-75 wt%, or <80 wt%, <70 wt%, or >40 wt%, or 45-75 wt%, or 50-65 wt%, based on the weight of the thermoplastic elastomer composition.
[0044] Modified HSBC (optional): In some embodiments, the thermoplastic elastomer composition further comprises a modified HSBC. A modified HSBC is defined herein as a functionalized block copolymer (FG-HSBC). In some embodiments, the HSBC is modified / functionalized (grafted) by incorporating functional groups into the base polymer. The functional groups are selected from monomers that are capable of reacting with the base polymer (e.g., reacting in solution or in the melt via a free radical mechanism).
[0045] In some embodiments, the monomer is ethylenically unsaturated to participate in free radical reactions. In some embodiments, by grafting unsaturated monomers with a slower polymerization rate, the resulting graft copolymer contains little or no homopolymer of the unsaturated monomer, and only contains short grafted monomer chains that do not separate into separate domains.
[0046] In some embodiments, the monomers used for functionalization have one or more functional groups or derivatives thereof in addition to at least one unsaturated point, such as carboxylic acid groups and their salts, anhydrides, esters, imide groups, amide groups, epoxy groups, acid chlorides, other polar moieties attached to ligands (which can be activated to form free radicals), etc. Examples include maleic acid, maleic anhydride, maleic esters, maleic amides, maleic imides, maleic hydrazides, fumaric acid, fumaric esters, fumaric amides, fumaric imides, itaconic acid, itaconic anhydride, itaconic esters, itaconic amides, itaconic imides, itaconic hydrazides, and mixtures thereof.
[0047] These functional groups can then react with other modifying materials to generate new functional groups. For example, the graft of an acid-containing monomer can be appropriately modified by esterifying the acid groups in the graft by appropriate reactions with hydroxyl-containing compounds of different carbon atom lengths. The reaction can be carried out simultaneously with the grafting or in a subsequent post-modification reaction.
[0048] In some embodiments, the modified hydrogenated styrenic block copolymer contains 0.02-20 wt%, or 0.1-10 wt%, or 0.2-5 wt%, or >0.5 wt%, or <15 wt%, or <20 wt% of maleic anhydride functional groups as grafted parts based on the total weight of the modified HSBC.
[0049] In some embodiments, based on the total weight of the thermoplastic elastomer composition, the content of the modified HSBC is 0-55 wt%, or 2-50 wt%, or 5-45 wt%, or 10-35 wt%, or 15-30 wt%, or 10-20 wt%, or 2-15 wt%.
[0050] Polypropylene (PP): The thermoplastic elastomer composition also includes polypropylene, polypropylene homopolymer. Polypropylene homopolymers suitable for the composition include any type of polypropylene, for example, the polypropylene homopolymer can be atactic polypropylene, isotactic polypropylene, hemi-isotactic polypropylene, syndiotactic polypropylene, or a combination thereof. A polymer is "random" when its side groups are arranged on both sides of the polymer chain in a random manner. In contrast, a polymer is "isotactic" when all of its side groups are arranged on the same side of the chain, and "syndiotactic" when its side groups alternate on opposite sides of the chain. In a hemi-isotactic polymer, there is a random substituent every other repeating unit.
[0051] In some embodiments, the polypropylene has a density of 0.85-0.99 g / cm2 as measured according to ASTM 1505. 3 , or <0.87g / cm 3 , or <0.08g / cm 3 , or <0.89g / cm 3 , <0.90g / cm 3 , or <0.99g / cm 3 , or <1g / cm 3 , and a softening point measured according to ASTM D3104 of 10-120°C, or <120°C, or <110°C, or <100°C, or <90°C, or <80°C, or <70°C.
[0052] In some embodiments, the polypropylene has a melt flow rate (MFR) measured according to ASTM D1238 at 230°C and 2.16 kg load of 3-60, or <60, or <55, or <45, or <35, or <25, or >2, or >5 g / 10 min.
[0053] In some embodiments, based on the total weight of the thermoplastic elastomer composition, the polypropylene is present in an amount of 8-60 wt%, or 15-50 wt%, or 15-40 wt%, or 20-40 wt%, or >13 wt%.
[0054] Thermoplastic polyurethane (TPU): The thermoplastic elastomer composition further comprises a thermoplastic polyurethane (TPU) compound. The TPU is selected from polyester-based TPU, polyether-based TPU, and combinations thereof. "Polyester-based" TPU refers to a TPU containing at least two ester groups and / or formed from reactants containing polyester bonds, while "polyether-based" TPU refers to a TPU containing at least two ether groups and / or formed from reactants containing polyether bonds.
[0055] TPU generally includes the reaction product of polyol and isocyanate. In some embodiments, TPU is polyester-based TPU, and includes the reaction product of polyester polyol and isocyanate. Suitable polyester polyol can be prepared by the reaction of dicarboxylic acid and diol with at least one primary hydroxyl group. Suitable dicarboxylic acid can be selected from but not limited to adipic acid, methyl adipic acid, succinic acid, suberic acid, sebacic acid, oxalic acid, glutaric acid, pimelic acid, azelaic acid, phthalic acid, terephthalic acid, isophthalic acid, and combinations thereof. The diol suitable for producing polyester polyol can be selected from but not limited to ethylene glycol, butanediol, hexanediol, bis (hydroxymethyl cyclohexane), 1,4-butanediol, diethylene glycol, 2,2-dimethylpropylene glycol, 1,3-propylene glycol, and combinations thereof.
[0056] In some embodiments, the TPU is a polyether-based TPU and includes a reaction product of a polyether polyol and an isocyanate. Suitable polyether polyols may be selected from, but are not limited to, polytetramethylene glycol, polyethylene glycol, polypropylene glycol, and combinations thereof.
[0057] In some embodiments, examples of suitable polyols include, but are not limited to, diols, polyester polyols, polyether polyols, modified polyether polyols, polyester ether polyols, castor oil polyols, polyacrylate polyols, and copolymers and mixtures thereof.
[0058] In some embodiments, the density of the TPU is 1-1.2 g / cm 3 , or <1.2g / cm 3 , or <1.15g / cm 3 , or <1.1g / cm 3, or >1g / cm 3 , measured according to ASTM D792.
[0059] In some embodiments, the content of the TPU is 0.1-15 wt%, or 1-12 wt%, or 2-12 wt%, or 0.2-5 wt%, or >0.5 wt%, or <15 wt% of the total weight of the thermoplastic elastomer composition.
[0060] Optional Components: The thermoplastic elastomer composition optionally comprises additional components including, for example, antioxidants, adhesion promoters, UV stabilizers, rheology modifiers, biocides, corrosion inhibitors, dehydrating agents, colorants (eg, pigments and dyes), fillers, surfactants, flame retardants, and combinations thereof.
[0061] In some embodiments, the antioxidant is selected from, but is not limited to, for example, pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 2,2'-methylenebis(4-methyl-6-tert-butylphenol), phosphites (including, for example, trinonylphenyl phosphite (TNPP) and bis(2,4-di-tert-butylphenyl) 4,4'-diphenyl diphosphonate), distearyl-3,3'-thiodipropionate (DSTDP), butylated hydroxytoluene (BHT), butylated hydroxyanisole (BHA), tert-butylhydroquinone (TBHQ), and combinations thereof.
[0062] In some embodiments, the optional components are present in an amount of 0-35, or 0.5-25, or 0.1-15, or 1-10, or 2-8, or <1, or <2, or <5 wt %, based on the total weight of the thermoplastic elastomer composition.
[0063] In some embodiments, the thermoplastic elastomer composition comprises 0-15, or 0.5-15, or 1-12, or <10, or <5, or <1 wt% plasticizer based on the total weight of the thermoplastic elastomer composition. In some embodiments, the composition is substantially free of plasticizer or oil (plasticizer is not intentionally added). In some embodiments, the plasticizer is selected from mineral oil, saturated hydrocarbons, naphthenic oil and paraffinic oil, oil with a certain aromatic content, and mixtures thereof.
[0064] Method for forming pellets or articles based on thermoplastic elastomer composition: In some embodiments, the various components of the thermoplastic elastomer composition are fed into a twin-screw extruder using a suitable device, such as a V-type mixer, a ribbon mixer, etc. The final mixture can be obtained by mixing the ingredients in a twin-screw extruder, a kneader, etc. Pellets, compounds or articles can be formed from the resulting mixed and melted mixture.
[0065] Properties of the thermoplastic elastomer composition and compounds prepared therefrom: The thermoplastic elastomer composition having improved mechanical and thermal properties suitable for high performance applications has one or more or all of the following properties:
[0066] The MFR (melt flow rate) measured according to ASTM D-1238 at 230°C and 2.16 kg load is 3-45, or 5-40, or 7-35, or 10-30, or 15-25, or >3, or >5, or >7, or >10, or >15, or <45 g / 10 min.
[0067] The tensile strength measured according to ASTM D-412 using Die C is 10-45, or 15-40, or 18-35, or >10, or >15, or >25, >35, or <45 MPa.
[0068] The elongation at break measured according to ASTM D-412 using Die C is 300-900%, or >300%, or >350%, or >400%, or >500%, or >550%, or >600%, or >700%, or >800%, or <900%.
[0069] The peel force (gf / 25mm) measured according to the 180° peel adhesion test performed on a galvanized steel substrate according to FTM 1 (300mm / min) is 45-300, or >45, or >50, or <300, or 75-150, or 100-200, or 205-250, or <275 gf / 25mm.
[0070] The hardness (Shore A) measured at 10 seconds by a ring and ball test according to ASTM D2240 is 40-95, or >40, or >45, or >55, or >60, or >75, or <95.
[0071] The tear strength (N / mm) measured according to ASTM D-624 using Die C is 45-120, or >45, >55, or >65, or >75, or >85, or >90, or <120 N / mm.
[0072] The tensile stress at 100% elongation measured according to ASTM D-412 using Die C is 8-25 MPa, or >8 MPa, or <25 MPa, or 10-18 MPa.
[0073] The tensile stress at 300% elongation measured according to ASTM D-412 using Die C is 8-25 MPa, or 10-18 MPa, or >8 MPa, or >10 MPa, or >12 MPa, or >15 MPa, or <25 MPa.
[0074] Application: The thermoplastic elastomer composition is suitable for applications that require adhesion to metal substrates and has excellent durability and heat aging resistance. Examples include elevator pulley linings, belts, synchronous belts, conveyor belts, seamless belts, transfer separation devices, charging devices, etc. Example
[0075] The following illustrative examples are non-limiting.
[0076] The following test method was used.
[0077] The glass transition temperature (Tg) was measured by dynamic mechanical analysis (DMA) according to ASTM 4065. The temperature sweep experiments were carried out in shear mode at a temperature of -80 to 200°C, a heating rate of 2°C / min and 10 r / s, unless otherwise specified, where the storage modulus (G'), loss modulus (G") and loss factor (tan δ) are functions of temperature.
[0078] Tensile stress strain was measured according to ASTM D412 using dumbbell C and a crosshead displacement speed of 500 mm / min. Melt flow rate (MFR) reported was measured according to D1238.
[0079] The components used in the examples include:
[0080] Antioxidant (AO): A sterically hindered phenolic primary antioxidant.
[0081] Polypropylene (PP): PP homopolymer having an MFR of less than 60 g / 10 min as measured according to ASTM D1238 and a density of 0.900 g / cm as measured according to ASTM D1505 3 of.
[0082] Polyether TPU: A thermoplastic polyurethane elastomer with a density of 1.15g / cm 3 , Shore A hardness of 96, tensile strength of 55MPa and elongation at break of 500%.
[0083] Polyester TPU: A thermoplastic polyurethane elastomer with a density of 1.2g / cm 3 , Shore A hardness of 95, tensile strength of 46.2MPa and elongation at break of 440%.
[0084] SEBSS - a hydrogenated styrene block copolymer (coupled) of the general formula (SE / B / S)nX having a vinyl aromatic content of 42 wt%, a Shore A hardness of 65, a peak molecular weight (Mp) of 140 kg / mol, a residual unsaturation of 0.1 meq / g, an Mp of the S block of 10.6 kg / mol, an MPa of the E / B / S block of 118.8 kg / mol (after coupling), and a molar ratio of E to B of 62:38.
[0085] FG-SEBSS: Maleated SEBSS (coupled) of the general formula MA-(SE / B / S)nX, having a vinyl aromatic content of 42 wt%, a Shore A hardness of 65, a peak molecular weight (Mp) of 140 kg / mol, a residual unsaturation of 0.1 meq / g, an Mp of the S block of 10.6 kg / mol, an Mp of the E / B / S block of 118.8 kg / mol (after coupling), a bound maleic anhydride content of 1.3 wt%, and an E to B molar ratio of 62:38.
[0086] Compounding of each formulation in Table 1 was carried out using a co-rotating twin screw extruder (TSE) with underwater pelletizing. The feed zone and mold temperatures were maintained at 180°C and 245°C, respectively. The pellets obtained were made into test plaques by injection molding. The nozzle temperature varied between 180°C and 245°C. The injection pressure of each formulation was adjusted to optimize the specimen appearance (no delamination) while eliminating flash during molding. The injection pressure varied from 15 psi to 58 psi depending on the formulation.
[0087] Table 1 contains the formulations of Examples 1-5 based on SEBS formulations with modified SEBS, PP, and TPU.
[0088] Table 1
[0089] Example 1 2 3 4 5 SEBSS (wt%) 50.1 47.6 45.1 47.6 45.1 Modified SEBSS (wt%) 5 5 5 5 5 PP (wt%) 44.8 42.3 39.8 42.3 39.8 Polyether TPU (wt%) - 5 10 - - Polyester TPU (wt%) - - - 5 10 Antioxidant (wt%) 0.1 0.1 0.1 0.1 0.1
[0090] Properties of samples (test plaques) prepared from Examples 1-5: Table 2 lists the properties of samples prepared from the formulations of Examples 1-5 in Table 1. Examples 1-5 show the same hardness for all tested samples, in the range of 87-90 Shore A. The melt flow rate (MFR) of Examples 1-5 at 230°C and 2.16 kg load is about 2 g / 10 min. Examples 2 and 4 with 5% polyether and polyester TPU show similar tensile properties (tensile modulus, ultimate elongation and tensile strength) and similar tear strength. Examples 3 and 5 with 10% higher TPU (polyether / polyester) show a decrease in tear strength and elongation at break. This decrease is observed at a load level of 5% when all the TPU reaches the surface. At a load level of 10%, there may be some residual TPU that is incompatible with SEBSS, resulting in reduced performance. Compared to Example 1 (without TPU), Examples 2-5 show a very high increase in peel force to a galvanized steel substrate as tested by a 180° peel test.
[0091] Table 2
[0092]
[0093] Although the terms "comprising" and "including" are used herein to describe various aspects, the terms "consisting essentially of" and "consisting of" may be substituted for "comprising" and "including" to provide more specific aspects of the present disclosure, and these aspects are also disclosed.
Claims
1. A thermoplastic elastomer composition comprising: a) 8-60 wt% of a polypropylene having a melt flow rate of 3-60 g / 10 min measured at 230° C. and 2.16 kg load according to ASTM D1238, and 0.85-0.99 g / cm 3 Density measured according to ASTM D1505; b) 2-12 wt% of thermoplastic polyurethane, wherein the thermoplastic polyurethane has a molecular weight of 1.0-1.2 g / cm 3 Density measured according to ASTM D792; c) 0-55 wt% of a modified hydrogenated styrenic block copolymer; and d) 38-75 wt% of a hydrogenated styrenic block copolymer; wherein the hydrogenated styrenic block copolymer is represented by at least one formula selected from the group consisting of SE / B / SS, (SE / B / S)nX and (SE / B / S)nX, wherein n is an integer of 2 to 30, X is a residue of a coupling agent, each block S is a polymer block composed of vinyl aromatic units and each block S has a peak molecular weight of 5 to 40 kg / mol as measured according to ASTM 5296-19, each block E / B / S is a copolymer block composed of ethylene units, butene units and vinyl aromatic units and each block E / B / S has a peak molecular weight of 35 to 300 kg / mol as measured according to ASTM 5296-19; The hydrogenated styrene block copolymer has the following properties: pass 1 The molar ratio of ethylene units to butene units measured by HNMR is 10:90-65:35, pass 1 The residual unsaturation measured by HNMR is <0.5 meq / g, pass 1 The total vinyl aromatic unit content (PSC) measured by HNMR is 25-65 wt%, and The peak molecular weight (Mp) measured according to ASTM5296-19 is 40-500 kg / mol; The thermoplastic elastomer composition has the following properties: The melt flow rate measured according to ASTM D-1238 at 230°C and 2.16 kg load is 1.0-45 g / 10 min, 40-100 Shore A hardness at 10 seconds as measured according to ASTM D-2240, and The peel force measured according to ASTM D-903 on galvanized steel substrates is 45-300 gf / 25mm.
2. The thermoplastic elastomer composition according to claim 1, wherein the content of the modified hydrogenated styrenic block copolymer is 2-15 wt%.
3. The thermoplastic elastomer composition according to any one of claims 1 to 2, wherein the modified hydrogenated styrenic block copolymer comprises at least one functional group selected from carboxylic acid groups and salts thereof, anhydrides, esters, imide groups, amide groups, epoxy groups and acid chlorides.
4. The thermoplastic elastomer composition according to claim 3, wherein the functional group is selected from maleic acid, maleic anhydride, maleic ester, maleic amide, maleic imide, maleic hydrazide, fumaric acid, fumaric ester, fumaric amide, fumaric imide, itaconic acid, itaconic anhydride, itaconic ester, itaconic amide, itaconic imide, itaconic hydrazide, and mixtures thereof.
5. The thermoplastic elastomer composition according to any one of claims 1 to 2, wherein the modified hydrogenated styrenic block copolymer is a maleic anhydride functionalized hydrogenated styrenic block copolymer having a maleic anhydride content of 0.1 to 10 wt %, based on the total weight of the modified hydrogenated styrenic block copolymer.
6. The thermoplastic elastomer composition according to any one of claims 1 to 2, wherein the total vinyl aromatic unit content of the hydrogenated styrenic block copolymer is 50 to 70 wt %, 1 HNMR measurements.
7. The thermoplastic elastomer composition according to any one of claims 1 to 2, wherein the hydrogenated styrenic block copolymer has a peak molecular weight (Mp) of 50 to 300 kg / mol, measured according to ASTM 5296-19.
8. The thermoplastic elastomer composition according to any one of claims 1 to 2, wherein the thermoplastic elastomer composition has the following properties: A melt flow rate of 1.0 to 8.0 g / 10 min at 230° C. and 2.16 kg load as measured according to ASTM D-1238, and The tensile stress at 100% elongation measured according to ASTM D-412 is 8-25 MPa.
9. The thermoplastic elastomer composition according to any one of claims 1 to 2, wherein the thermoplastic elastomer composition has an elongation at break of 500 to 900%, measured using Die C according to ASTM D-412.
10. The thermoplastic elastomer composition according to claim 1, wherein the thermoplastic polyurethane is selected from the group consisting of polyether-based thermoplastic polyurethane, polyester-based thermoplastic polyurethane, and mixtures thereof.
11. The thermoplastic elastomer composition according to claim 1, wherein the polypropylene has a molecular weight of 0.85-0.99 g / cm 3 Density measured according to ASTM D1505.
12. The thermoplastic elastomer composition according to claim 1, wherein the polypropylene has a softening point of 10-120°C as measured according to ASTM D3104.
13. The thermoplastic elastomer composition according to any one of claims 1 to 2, wherein the thermoplastic elastomer composition further comprises 0 to 15 wt% of mineral oil.
14. An article comprising the thermoplastic elastomer composition of any one of claims 1 to 13.
15. The article of claim 14, which is used as an elevator pulley lining, a belt, a timing belt, a conveyor, a seamless belt, a transfer separation device or a charging device.